Formulation and Characterization of Chitosan Based Dexibuprofen Nanoparticles Using Ionotropic Gelation Method: Pharmaceutical Science-chitosan based Nanoparticle for better anti- inflammatory therapy - S.Vivekanandan; Berit Lindholm; K.Raghunandan Reddy; P. Venkatesan (International Journal of Life Science and Pharma Research, 2022)
Dexibuprofen is a pharmacologically active enantiomer of racemic ibuprofen (NSAID), which is used to treat pain and inflammation. Like common NSAIDs, Dexibuprofen is an active enantiomer of ibuprofen that suppresses the prostanoid synthesis in the inflammatory cells via inhibition of the COX-2 isoform of the arachidonic acid COX. The therapeutic use of Dexibuprofen is limited by the rapidity of the onset of its action and its short biological half-life. Hence, our aim was to develop Dexibuprofen nanoparticles formulation to overcome these disadvantages using optimized concentration of polymers by appropriate methods for nanoparticle preparation. The drug and the nanoparticle formulation of Dexibuprofen F11 were comparatively assessed for FT IR spectrums by using FT-IR method. The DSC study was used as one of the tool to assess the compatibility between drug and the excipients. As per DSC thermograms, the drug as well as drug with mixture of excipients chitosan, sodium tripolyphosphate had shown no interactions with dexibuprofen. The ionotropic gelation method was used to prepare Dexibuprofen nanoparticles. The chitosan and sodium tripolyphosphate (TPP) of different concentrations were used as polymers to prepare Dexibuprofen nanoparticles. Total eleven different formulations were explored with different concentrations of drug : polymer ratios using ionotropic gelation method to identify optimal concentrations of polymer. Among different formulations, F11 formulation with optimized concentration of 5% chitosan and 1% Sodium tripolyphosphate polymers along with Dexibuprofen showed maximum drug release. The objective was to evaluate the developed Dexibuprofen nanoparticles. In-vitro drug release was evaluated in 0.05M phosphate buffer pH7.2 and found that the drug release of F11 formulation of Dexibuprofen nanoparticle had shown release till 24 hours more than that of other trials. Hence, F11 formulation was considered as the optimized nanoparticle formulation to control drug release till 24 hours. The entrapment efficacy of the formulated Nanoparticles was found to be in the range of 75.48%-91.22% respectively.